On Solutions of a Quadratic Integral Equation of Urysohn Type - Lamyaa Sadoon (College of Education for Pure Sciences, 2014)
In this paper, we investigate the existence of a unique solution on a semi-infinite interval for a quadratic integral equation of Urysohn type in Frechet space using a nonlinear alternative of Leray-Schauder type for contraction maps.